A field study of indoor air quality and occupant perception in experimental laboratories and workshops. Issue 2 (2nd October 2018) - Kwong, Qi Jie; Abdullah, Jamalunlaili; Tan, Sheng Chuan; Thio, Tzer Hwai Gilbert; Yeaw, Win Shyang
Abstract : Purpose: Maintaining good indoor air quality (IAQ) in the built environment is essential to assure health, safety and productivity of occupants. The purpose of this paper is to report on the preliminary IAQ assessment of selected air-conditioned laboratories and naturally ventilated workshops in a tropical education institution. Design/methodology/approach: The concentration levels of five major indoor air pollutants (IAPs) – carbon dioxide, carbon monoxide, respirable particulates, formaldehyde (HCHO) and total volatile organic compounds (TVOC) in each sampling area were measured using calibrated air sampling sensors and the tracer-gas analysis was used to determine the ventilation effectiveness. A questionnaire survey was carried out concurrently to study the prevalence of sick building syndrome (SBS) among users of laboratories and workshops and the data collected were statistically analysed using χ 2 test. Findings: The air pollutant levels were found to be below the threshold limit values set in the local code of practice on IAQ, except for two of the air-conditioned laboratories. This is possibly due to insufficient ventilation, smaller floor area per occupant ratio, long-term exposure to chemical substances, and improper disposal of the used chemical substances. The total particulate levels were higher in naturally ventilated workshops because such spaces were assigned for mechanical works which involved grinding, welding and fabrication. Besides, it was identified that most of the air contaminant levels were not normally distributed ( p <0.05) within the sampling areas and SBS like dry eyes, watery eyes, tiredness and dry throat were reported in both laboratories and workshops. The outcomes of this work suggest that an increase of ventilation rate was necessary to reduce the concentration of the IAPs in air-conditioned laboratories and improved housekeeping would help mitigate the prevalence of SBS symptoms. Research limitations/implications: This research was carried out in selected laboratories and workshops in a Malaysian educational institution and only five major IAPs stipulated in the Department of Occupational Safety and Health (DOSH) code of practice were measured. Practical implications: The results of this study will enable facility engineers and managers to understand the IAPs concentration levels and potential SBS problems in academic laboratories and workshops. The recommended strategies can be considered to improve IAQ conditions in such spaces. Originality/value: Most of the previously conducted IAQ studies focused only on commonly occupied building spaces such as offices, classrooms and houses. Information of the quality of air and SBS conditions in experimental facilities in developing nations that is available is currently very limited. This case study provides detailed information on IAQ in laboratories and workshops in Malaysia with focuses on the concentration levels of particular harmful gases, the prevalence of SBS among users of these facilities and the appropriate mitigation strategies. The results presented are of value to both academic and industry communities.